Can indolebutyric and fulvic acids induce adventitious rhizogenesis on mini-cuttings from Brazilian native tibouchinas? - Latoh, Leandro Porto; Gomes, Erik Nunes; Zuffellato-Ribas, Katia Christina (Ornamental Horticulture, 2019)
The use of Brazilian native species for ornamental purposes is a promising alternative for local floriculture. Seeking to contribute with new information in this context, the present study aimed to evaluate the rooting performance of mini-cuttings from three Tibouchina species (T. aff. fothergillae, T. heteromalla and T. moricandiana var. vinacea) as affected by the use of indolebutyric acid (IBA) and fulvic acid (FA). Mini-cuttings with 5 cm in length were prepared with plant material from clonal mini-hedges and submitted to different treatments as follows: control treatment (T1); 2,000 mg L-1 IBA (T2); 2,000 mg L-1 FA (T3) and 2,000 mg L-1 IBA + 2,000 mg L-1 FA (T4). Planting was carried out in plastic containers filled with vermiculite, and, after 26 days under greenhouse conditions, the following variables were evaluated: mini-cuttings rooting percentage (RP), roots number (RN), roots length (RL), initial leaves maintenance (ILM) and sprouting (SP). The experiment was conducted under a completely randomized design in a 3 x 4 factorial scheme, with four replications and 20 minicuttings per plot. Rooting percentages were higher than 90% in all three species, regardless of IBA or FA treatments. RP, ILM and SP did not show statistically significant interaction between the treatments. For RN, T2 and T4 promoted the best results on T. aff. fothergillae (12.62 and 14.92, respectively) and T2 resulted in maximum values for T. heteromalla (15.65). For RL, T2 and T4 were statistically superior on T. heteromalla (9.52 and 8.20 cm, respectively). The use of IBA and FA is dispensable for rhizogenesis induction on mini-cuttings from the studied species